DENSIDADE DE SEMEADURA PARA A CULTURA DO AMENDOIM NA REGIÃO DO BOLSÃO SUL-MATO-GROSSENSE - RIBEIRO, Eduarda Barbosa Esteves; NOGUEIRA, Lavínia Rodrigues; SERON, Cássio de Castro; ARAÚJO, Suleiman Leiser; MARTINS, Murilo Battistuzzi; VENDRUSCOLO, Eduardo Pradi (ANAIS DO ENIC, 2025)
-